Impulse Buying Behaviors in Live Streaming Shopping Using the Stimulus-Organism-Response Framework - Violin Tri Wulandari; Varell Alkhafi; Faranita Mustikasari (Business Education Program of Universitas Pendidikan Indonesia, 2023)
Live streaming shopping, characterized by its attributes of authenticity, visualization, and interactivity, plays a pivotal role in e-commerce (Hu Chaudhry, 2020). This emerging retail phenomenon empowers consumers with direct access to information and fosters heightened engagement with the promoted products, as underscored by Todd and Melancon (2018). This study investigates the impact of various stimuli, encompassing internal factors (individual characteristics, situational stimuli, social media influences) and external factors (marketing stimuli) as independent variables. It further explores the mediating role of hedonic motivation and its influence on impulsive buying, serving as the dependent variable. This study uses a quantitative approach to target TikTok users in the Indonesian population. Sample selection employs purposive sampling, while data analysis utilizes Structural Equation Modeling-Partial Least Squares (SEM-PLS) and SMART PLS software. The findings reveal a positive correlation between individual characteristics, situational, social media, and marketing stimuli with hedonic motivation. Moreover, hedonic motivation is positively associated with impulsive buying behavior.